HARMFUL SIDE EFFECTS OF BROAD-SPECIFIC ANTIBIOTICS (Multidisciplinary Journal of Science and Technology, 2026)
This article provides an in-depth analysis of the problems associated with the use of broad-spectrum antibiotics in clinical practice and their negative effects on the human body. The mechanisms of antibiotic resistance, imbalance of normal microbiota (dysbacteriosis), allergic reactions, toxic effects (hepatotoxicity, nephrotoxicity, ototoxicity), and the pathophysiological basis for the development of superinfection resulting from uncontrolled and unreasonable use of antibiotics are highlighted.            The drug-drug interactions of broad-spectrum antibiotics and complications arising in polypharmacy are also considered. The article scientifically substantiates the need for rational use of antibiotics, i.e. an individual approach, therapy based on microbiological tests, and giving preference to narrow-spectrum drugs.            This work serves to highlight the current problems aimed at improving the culture of antibiotic use in modern medicine, preventing the development of resistance, and ensuring patient safety.